Extending the ground of public confidence : teaching civil liberties in K-16 social studies education - Hubbard, Janie (Teaching and learning social studies., 2019)
"In these times and for future generations, students must learn how to analyze constantly changing issues, decipher media as truth or fake news, and contest highly competitive, biased informational sources. Students must develop knowledge, skills, and attitudes necessary for leveraging their capacity as active citizens charged with holding institutions accountable for truthfully addressing and protecting civil liberties. Extending the Ground of Public Confidence: Teaching Civil Liberties in K-16 Social Studies Education is a book grounded in current scholarship and seeks to address the need for a practical, user-friendly resource for teaching civil liberties in K-12 social studies and teacher education. This book brings together chapter-length discussions about various issues, introduced first from historic perspectives and then compared and described in modern terms. Such topics include, though are not limited to, disputes surrounding freedom of speech and religion, power issues, defending property rights, debates on security of persons and privacy, free exercise of assembly and expression, and the endless debate about who can and cannot vote in U.S. elections. Each chapter contains teaching-ready, inquiry-based learning activities framed by the National Council for the Social Studies (NCSS) College, Career, and Civil Life (C3) Inquiry Arc (2013). Students (1) develop questions and plan investigations; (2) apply disciplinary concepts and tools; (3) gather, evaluate and use evidence; and (4) work collaboratively to communicate conclusions and take informed action. Lesson ideas engage learners across age groups and grade levels in learning that fosters informed, sustainable actions aimed at upholding and protecting civil liberties"--